Efficacy of ultrasonography for structural categorisation of abnormal uterine bleeding - Rathi, Jyoti; Wagh, Girija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Abnormal uterine bleeding (AUB) is defined as bleeding from the uterine corpus endometrium to be precise, the bleeding is abnormal in regularity, volume, frequency, or duration. The international federation of gynecology and obstetrics (FIGO) categorized AUB based on structured medical history, laboratory tests, ultrasound, and or hysteroscopy-based techniques.The classification is based on the phrase "PALM- COEIN", (pronounced “pahm-koin”) of which "PALM" represents polyp, adenomyosis, leiomyoma, malignancy (and hyperplasia) and defines structural pathologies that can be assessed visually. Transvaginal ultrasound (TVS) is the first-line imaging test for the evaluation of abnormal uterine bleeding in both premenopausal and postmenopausal women. The purpose of this study was to estimate the diagnostic effectiveness of two-dimensional ultrasound (TAS and TVS) in assessing the structural causes of AUB and to compare the histopathological and intraoperative findings with ultrasound. Methods: It was a prospective observational study. A total of 200 women presenting with abnormal uterine bleeding between the age group of 18-55 years were included in study. All patients were subjected to routine investigations for AUB and ultrasonography (USG). Wherever appropriate the findings of USG were compared with intra-operative and histopathology findings. Results: Diagnostic accuracy of USG was 78.1% with sensitivity and specificity of 88.5% and 60%. Positive predictive value (PPV) and negative predictive value (NPV) was 79.4% and 75%. USG is a simple, safe, fast, efficient and tolerable procedure. In diagnosing structural uterine pathology responsible for abnormal uterine bleeding, it has outstanding diagnostic accuracy and should be followed in all such cases. Conclusions: We cannot be definitive in our approaches always, USG act as a wonderful modality to help us not only in identifying the structural causes but also the functional causes. However, the gold standard of identifying endometrial pathology is histopathology and it can’t be replaced by anything.